Os efeitos da adaptação do PECS associada ao Curriculum funcional natural em pessoas com autismo infantil - Walter, Catia Crivelenti de Figueiredo (2000)
Communication disorders in persons diagnosed with autism, generally are severe and bring difficulties to their interpersonal relationships, putting them apart, being not comprehended by the majority of other people. The main objective of this study was to evaluate the effects of the adaptation of the Picture Exchange Communication System (PECS) applied in the context of a natural functional curriculum (adapted PECS) in the communication of persons diagnosed as autistic, who do not presented oral language and/or functions speech at the beginning of the study. As a secondary objective, the study had the intention to verify if the adapted PECS would help the participants to begin to use of speech. The study was conducted at Centro Ann Sullivan do Brasil (CASB), located in Ribeirão Preto City São Paulo State. In order to verify the effects of the intervention, an AB simple subject research design was applied and replicated within four boys with ages varying from 5 to 8 years old, diagnosed as autistic. The study involved two phases: baseline and intervention. In order to train the 5 phases of the adapted PECS, the PCS (Picture Communication System) pictures was used. The training and data collection sessions were held during 2 years. The results showed that all participants presented changes in their communicative behavior and acquired an expressive vocabulary in some words, some sounds and in the use of pictures, that varied from 25 to 61, all being used with communicative function. The obtained data suggests that the use of pictures with interaction and solicitation objective of something very much desired, seems to contribute to the emission of speech, sounds and gestures, used with communicative function by the participants. However, other studies must be encouraged, as well as the adapted PECS extension to persons with different diagnoses, who are able to benefit from any alternative communication system. The study concludes, since the PECS communication system has a basic element the interested picture exchanging by the participants through an interactive action, could contribute, in the future, to the inclusion process, not only at school environment, but also to home and community